Dysfunction in inhibition and executive capabilities in children with autism spectrum disorder: An eye tracker study on memory guided saccades. Issue 2 (3rd April 2023) - Caldani, Simona; Humeau, Elise; Delorme, Richard; Bucci, Maria Pia
Abstract: Background: Dysmetria in children with autism spectrum disorders is considered depend on executive dysfunctions. To explore the impact of inhibitory control and working memory on oculomotor performance in children with autism spectrum disorder (ASD), we used the memory guided saccade (MGS) paradigm. Method: We enrolled in our study a group of 26 children with ASD and in a group of 26 children age-, sex-, and IQ-matched of with typically development, using only one single delay period and one single stimulus amplitude. We recorded with a video eye-tracker system- the latency and the accuracy of the MGS as well as the number of anticipatory saccades during the MGS paradigm. Results: Children with ASD displayed significant increased latency ( p < .01), decreased amplitude of memory guided saccades ( p < .01) and an elevated number of anticipatory saccades ( p < .003), when compared to age-, sex-, IQ- matched children with typical development. Conclusion: These abnormalities may underline the executive dysfunctions frequently reported in ASD: the increased latency and the decreased amplitude of memory guides saccades may be related to planning and working memory impairments; the increased number of anticipatory saccades may be linked to a deficit in inhibitory control.